Types of Questions Used in the Teaching of Short Stories - Harvindar, Kaur (2012)
Critical and creative thinking skills are two of the criteria required in the Malaysian English Language Syllabus. Teachers are required to infuse these skills in the teaching and learning of the English language in Malaysian classrooms. One of the ways this can be done is through questioning. Thus, this study investigates at the types of questions employed by the teachers teaching short stories in the literature in English component in the form 4 syllabus. The data for this study were collected using observations with three form 4 teachers for a duration of 5 weeks. The data were analysed using the Barrett’s Taxonomy of reading comprehension. The findings of the study indicate that there is a tendency for teachers to employ questions of lower-order thinking as compared to questions of higher-order thinking. This study recommends that the teachers be provided with specific trainings on how to pitch their questions to inculcate critical and creative thinking skills in their learners.